UKRAINIAN-LANGUAGE TEXTS IN THE “TOWN BOOK OF KOLOMYA 1769–1771”: LINGUISTIC ASPECT - Rusakova, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
The article presents a linguistic analysis of two recently discovered small-sized texts of a letter and an oath, dated 1768 and 1771, which reflect the living Ukrainian speech of the mid-18th century. These texts were first published in 2025 in the “City Book of Kolomyia 1769–1771”, which contains a total of 144 act entries in Old Polish and Latin. Based on the analysis of the grammatical structure of the language of the letter and the oath, it was found that these texts have features of the southwestern dialect of the Ukrainian language, although they are written in the Latin script of the Polish model. The analyzed fragments present the oldest linguistic features of the Ukrainian language, inherited from the Proto-Slavic language, which testifies to the continuous development of the Ukrainian language over the millennium.